2021
DOI: 10.1029/2021gl093841
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Climate Responses to Recent Australian Wildfire and COVID‐19 Emissions Anomalies Estimated in CESM2

Abstract: Multiple episodes of anomalous climate forcing have occurred in recent years. These include the biomass burning emissions anomalies from the 2019-2020 Australian wildfire season (hereafter referred to as AF), and anthropogenic emissions perturbations arising from the response to the spread of the Coronavirus Disease 2019, which began in Jan 2020 and continues through the present (hereafter referred to as COVID). While significant efforts have been made for diagnosing the climate effects of these events, unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 37 publications
3
20
0
Order By: Relevance
“…The gray shaded region represents the range of stochastic variability of the control ensemble while the colored shaded region provides a measure of the combined uncertainty on the anomaly. In the first 6 months after the event, temperature anomalies points to cooling at values of (negative) 0.1-0.2 K (see also Fasullo et al, 2021). During the same period, the radiative forcing perturbation reaches a minimum (i.e., a maximum in magnitude) in February, at about −3 W/m 2 , in agreement with observational assessments (Khaykin et al, 2020).…”
Section: Models Of the Nswv19/20 Eventsupporting
confidence: 79%
“…The gray shaded region represents the range of stochastic variability of the control ensemble while the colored shaded region provides a measure of the combined uncertainty on the anomaly. In the first 6 months after the event, temperature anomalies points to cooling at values of (negative) 0.1-0.2 K (see also Fasullo et al, 2021). During the same period, the radiative forcing perturbation reaches a minimum (i.e., a maximum in magnitude) in February, at about −3 W/m 2 , in agreement with observational assessments (Khaykin et al, 2020).…”
Section: Models Of the Nswv19/20 Eventsupporting
confidence: 79%
“…United Nations Environment Programme, 2020Programme, , 2021. Although previous studies have revealed slight effects of reduced emissions associated with Covid-19 containment on the global mean values of radiative forcing, surface air temperature, and precipitation (Fasullo et al, 2021;Gettelman et al, 2020;Weber et al, 2020), but these decreased emissions contributed importantly to the 2020 extreme summer rainfall at the regional scales (Fadnavis et al, 2021;Y. Yang et al, 2022).…”
mentioning
confidence: 86%
“…The impact of Covid‐19 on emissions is expected to continue, since the Covid‐19‐related rescue spending and recovery investment have set out in a low‐carbon way in several countries, such as China, Germany, and the United Kingdom (Keramidas et al., 2021 ; United Nations Environment Programme, 2020, 2021). Although previous studies have revealed slight effects of reduced emissions associated with Covid‐19 containment on the global mean values of radiative forcing, surface air temperature, and precipitation (Fasullo et al., 2021 ; Gettelman et al., 2020 ; Weber et al., 2020 ), but these decreased emissions contributed importantly to the 2020 extreme summer rainfall at the regional scales (Fadnavis et al., 2021 ; Y. Yang et al., 2022 ). Moreover, stronger climate responses may emerge if the economic stimulus policies at post‐pandemic result in persistent changes in anthropogenic emissions (Forster et al., 2020 ; Y. Yang et al., 2020 ; Z. L. Wang et al., 2016 ).…”
Section: Introductionmentioning
confidence: 95%
“…In comparison, the 2019 Australian Wildfire event induced a larger SWF of approximately −0.95 W/m 2 , about five times larger than the SWF anomaly caused by the 10 Gg/yr emission scenario. However, the Australian fire event's SWF climate response lasted for a couple months before tapering off (Fasullo et al, 2021).…”
Section: Climate Response Scaling With Increased Emissionsmentioning
confidence: 99%
“…Both the 30 and 100 Gg simulations experience a statistically significant surface cooling of approximately −0.08 K and −0.2 K, respectively. For a frame of reference, the 2019 Australian wildfire event, which injected approximately 20 Gg of BC into the lower stratosphere produced a 0.06 K global cooling signal that lasted only a few months (Fasullo et al, 2021).…”
Section: Climate Response Scaling With Increased Emissionsmentioning
confidence: 99%